Nekustamo īpašumu cenu ietekmējošie faktori - Pīlēns, Reinis (Latvijas Universitāte, 2023)
Bakalaura darba tēma ir “Nekustamo īpašumu cenu ietekmējošie faktori”. Bakalaura darbs tika izstrādāts ar mērķi veikt nekustamo īpašumu tirgus tendenču un cenu ietekmējošo faktoru analīzi, kā arī identificēt būtiskāko faktoru ietekmi uz Rīgas dzīvokļu cenām. Bakalaura darba pirmajā daļā ir izteikts nekustamo īpašumu tirgus dalībnieku iedalījums, aprakstīti pamata tirgus spēku, pieprasījuma un piedāvājuma darbības specifika, kā arī šī tirgus attīstīšanās pamatnosacījumi. Otrajā daļā no dažādiem skatu punktiem un tiek izpētītas Latvijas nekustamo īpašumu tirgus attīstības tendences. Trešajā daļā tiek veikta uz nekustamo īpašumu novērtēšanas metodoloģijas balstīta faktoru ietekmes noteikšana Rīgas dzīvokļu piedāvājumam

The bachelor thesis deals with Riga's real estate - it examines the price determinants of apartments in Riga and analyses the current state of the real estate market in Riga. In the first part of the bachelor's thesis, the author describes theoretical aspects of the real estate market - what causes shifts in supply and demand, how the market responds to these changes, what are the premises for development, and how properties are evaluated based on econometric models. Part two is devoted to the analysis of the current state of the real estate market in Latvia. The author describes the current tendencies from a macroeconomic perspective that examines the effects of factors, such as inflation, income, interest rates, and more. The third part addresses housing market in Riga. The emphasis is on apartment supply analysis in different neighbourhoods. Apart from describing collected data, the author examines various factors that affect apartment pricing and measures their magnitude of influence. Finally, the author concludes the research and makes recommendations that highlight areas for development in Riga real estate market.
Factors affecting housing prices
Keywords: Ekonomika; nekustamie īpašumi; ietekmējošie faktori; regresijas analīze; statistika